Performance of Trichopria drosophilae (Hymenoptera: Diapriidae), a Generalist Parasitoid of Drosophila suzukii (Diptera: Drosophilidae), at Low Temperature. Issue 3 (27th May 2020) - Colombari, Fernanda; Tonina, Lorenzo; Battisti, Andrea; Mori, Nicola
Abstract: Survival and parasitism activity of Trichopria drosophilae Perkins adults, a cosmopolitan parasitoid of Drosophila spp., were studied under laboratory conditions using five constant temperatures at the lower range known for this enemy, from 4 to 20°C in 4°C increments. Drosophila suzukii Matsumura, an invasive pest of small fruits, was used as a host. Commercially available adult parasitoids were provided with 1) food and D. suzukii pupae; 2) food and no D. suzukii pupae; 3) no food and no pupae. The results show that adult females of T. drosophilae lived longer than males, and both generally benefitted from food supply. The highest level of survival was observed between 8 and 12°C for fed insects, irrespective of whether they were offered host pupae or not. The absence of food led to the highest mortality, but the parasitoid demonstrated considerably resistance to prolonged starvation. Successful parasitism increased steadily with temperature and reached the highest value at 20°C. Conversely, D. suzukii emergence rate was high after exposure of pupae to parasitoids at 4°C, while pupal mortality increased strongly with temperature until 12°C. The findings indicate that T. drosophilae is well adapted to the relatively cold conditions experienced in early spring and in autumn or at high elevations, when the host pupae could be largely available. The long lifespan of the adults and the ability to parasitize the host at low temperature make T. drosophilae potentially useful for the biocontrol of D. suzukii .